2007
DOI: 10.1021/jf071569n
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Combination of Fucoxanthin and Fish Oil Attenuates the Weight Gain of White Adipose Tissue and Decreases Blood Glucose in Obese/Diabetic KK-Ay Mice

Abstract: Fucoxanthin is a marine carotenoid found in edible brown seaweeds. We previously reported that dietary fucoxanthin attenuates the weight gain of white adipose tissue (WAT) of diabetic/obese KK- A(y) mice. In this study, to evaluate the antiobesity and antidiabetic effects of fucoxanthin and fish oil, we investigated the effect on the WAT weight, blood glucose, and insulin levels of KK- A(y) mice. Furthermore, the expression level of uncoupling protein 1 (UCP1) and adipokine mRNA in WAT were measured. After 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
199
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(213 citation statements)
references
References 34 publications
10
199
2
2
Order By: Relevance
“…The above results supplement previous work on S. polycystum, which was reported to reduce blood glucose and plasma insulin levels in diabetic/obese mice (Maeda et al 2007). The phytochemicals and soluble fibres present in the extracts of S. polycystum have cholesterol-lowering effects and affect intestinal glucose absorption (Taskinen 2002;Vaugelade et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…The above results supplement previous work on S. polycystum, which was reported to reduce blood glucose and plasma insulin levels in diabetic/obese mice (Maeda et al 2007). The phytochemicals and soluble fibres present in the extracts of S. polycystum have cholesterol-lowering effects and affect intestinal glucose absorption (Taskinen 2002;Vaugelade et al 2000).…”
Section: Discussionsupporting
confidence: 91%
“…in a previous study, we demonstrated that fucoxanthin, the active component in Wls, has an anti-obesity effect (5). The main mechanism of this effect was shown to be the induction of ucP1 in WaT by fucoxanthin.…”
mentioning
confidence: 73%
“…Fucoxanthin is a characteristic carotenoid of brown algae including edible species such as Undaria pinnatifida and Hijikia fusiformis. We recently reported the suppression of the development of white adipose tissue (WaT) by fucoxanthin in obese/diabetic kk-A y mice (4,5). expression of uncoupling protein 1 (ucP1), which plays an important role in energy expenditure, was induced by dietary fucoxanthin in WaT but not in brown adipose tissue; this ucP1 expression was responsible for the antiobesity effect of fucoxanthin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucoxanthin shows anti-diabetic effects by changing of adipocyte cell properties 11,12,18 . KK-A y mice not only developed obesity, but also developed hyperglycemia and hyperinsulinemia along with insulin resistance.…”
Section: Anti-diabetic Effects Of Fucoxanthinmentioning
confidence: 99%